The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.2298/tsci1804645g
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of polyethylene terephthalate treated by supercritical CO2

Abstract: Structure and properties of polyethylene terephthalate were characterized by SAM, Fourier transform infrared spectrometry, X-ray diffraction, and thermal analysis to evaluate the effect of supercritical CO 2 on the structural behavior. The dynamic shrinking behavior of polyethylene terephthalate was analyzed using the Kelvin-Voigt model. The results indicated that uneven and significantly different surface of the polyethylene terephthalate fiber was displayed since the spinning oil and other additives added in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…As shown in Figure A, all PET samples exhibited the characteristic assigned vibrations for PET functional groups −OH stretch (3424 cm –1 ), CH 2 stretch (2962 cm –1 ), CH 3 stretch (2904 cm –1 ), CO stretch of carbonyl (1712 cm –1 ), CC stretch of aromatic ring (1504 cm –1 ), −CH 2 bending (1453 cm –1 ), aromatic skeleton stretch (1408 cm –1 ), C–H in-plane bend of alkyl (1338 cm –1 ), C(O)-O stretch or ring-ester C–C stretch (1238 cm –1 ), ring C–H bend in plane or ring C–C stretch (1120 cm –1 ), C–O stretch (1091 cm –1 ), ring C–H in-plane stretch (1014 cm –1 ), O–CH 2 stretch (970 cm –1 ), ring C–H out of plane bend or ring-ester C–C out of plane bend (870 cm –1 ), and ring C–H out-of-plan bend (721 cm –1 ). , However, for scCO 2 -treated PET, high energy shifts were observed which corresponded to −CH 2 bending (1453 to 1454 cm –1 ), C(O)-O stretch or ring-ester C–C stretch (1238 to 1244 cm –1 ), ring C–H in-plane stretch (1014 to 1016 cm –1 ) and C–O stretch (1091 to 1094 cm –1 ) (Figure B). These shifts can be due to the rearrangement of polymer chains during recrystallization of PET′s amorphous regions during treatment and/or cryogrinding. , Using 2D FTIR, Chen et al, reported that high energy shifts can be observed when amorphous regions are transformed into more crystalline conformation regions …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure A, all PET samples exhibited the characteristic assigned vibrations for PET functional groups −OH stretch (3424 cm –1 ), CH 2 stretch (2962 cm –1 ), CH 3 stretch (2904 cm –1 ), CO stretch of carbonyl (1712 cm –1 ), CC stretch of aromatic ring (1504 cm –1 ), −CH 2 bending (1453 cm –1 ), aromatic skeleton stretch (1408 cm –1 ), C–H in-plane bend of alkyl (1338 cm –1 ), C(O)-O stretch or ring-ester C–C stretch (1238 cm –1 ), ring C–H bend in plane or ring C–C stretch (1120 cm –1 ), C–O stretch (1091 cm –1 ), ring C–H in-plane stretch (1014 cm –1 ), O–CH 2 stretch (970 cm –1 ), ring C–H out of plane bend or ring-ester C–C out of plane bend (870 cm –1 ), and ring C–H out-of-plan bend (721 cm –1 ). , However, for scCO 2 -treated PET, high energy shifts were observed which corresponded to −CH 2 bending (1453 to 1454 cm –1 ), C(O)-O stretch or ring-ester C–C stretch (1238 to 1244 cm –1 ), ring C–H in-plane stretch (1014 to 1016 cm –1 ) and C–O stretch (1091 to 1094 cm –1 ) (Figure B). These shifts can be due to the rearrangement of polymer chains during recrystallization of PET′s amorphous regions during treatment and/or cryogrinding. , Using 2D FTIR, Chen et al, reported that high energy shifts can be observed when amorphous regions are transformed into more crystalline conformation regions …”
Section: Resultsmentioning
confidence: 99%
“…These shifts can be due to the rearrangement of polymer chains during recrystallization of PET′s amorphous regions during treatment and/or cryogrinding. 58,59 Using 2D FTIR, Chen et al, reported that high energy shifts can be observed when amorphous regions are transformed into more crystalline conformation regions. 58 In addition, possible changes in chemical interactions induced by scCO 2 were studied by 1 H NMR (Figure 10).…”
Section: Effect Of Scco 2 Pretreatment Followed By Cryogrinding On En...mentioning
confidence: 99%
“…The diffusion coefficients of water and ethanol in swollen PVA increase linearly with the degree of swelling. Shanks and Pavel [ 22 , 23 , 24 , 25 ] used MD simulation to study the diffusion of methane and other gases and small molecule penetrants in aromatic PET, amorphous PET, and isomeric PET. They found that the diffusion coefficient and free volume and its distribution are related.…”
Section: Introductionmentioning
confidence: 99%